STRENGTHENING OF REINFORCED CONCRETE BEAM ELEMENTS USING ROD-FORM COMPOSITE MATERIALS - Slobodan Ranković; Radomir Folić; Marina Mijalković; Žarko Petrović (Facta Universitatis. Series: Architecture and Civil Engineering)
The paper emphasizes the advantages of using FRP (fiber reinforced polymer) materials for strengthening reinforced concrete structures. The results of experimental research on the effects of strengthened reinforced concrete beam elements exposed mainly to bending using FRP rod-shaped elements are presented. The load disposition (experimental setup) was in accordance with the "four point load" scheme, and the measurements were made using modern measuring techniques. The results regarding the increase in the bearing capacity of strengthened beams using the NSM (near surface mounting) and EB (externally bounding) methods were compared. In particular, the load-deflection ratio until failure was analyzed, as well as the change in stiffness depending on the load level. It has been shown that the load capacity of beams strengthened with carbon fiber rods (NSM CFRP) increases by 89%, and the load capacity of beams strengthened with glass fiber rods (NSM GFRP) by 73%. The bearing capacity of beams strengthened with EB CFRP laminates increases by 51%. The ductility of strengthened beams was analyzed and it was shown that it is higher when using GFRP rod-shaped elements (DI=6.5) compared to CFRP rods (DI=5.3). The ductility of the beams strengthened by the EB CFRP method was not satisfactory (DI=2.6).